A numerical study on the effects of a midlatitude upper-level trough on the track and intensity of Typhoon Bavi (2020) - Wang, Hui; Yu, Yubin; Xu, Hongxiong; Zhao, Dajun; Liang, Jia (Frontiers in Earth Science, 2023)
The complex interactions between a tropical cyclone (TC) and the midlatitude upper-level trough or cutoff low (sometimes called cold-core vortex) can lead to unusual track, such as sudden turning motion, and intensity change of the TC, often leading to large forecast errors. In this study, the track and intensity changes of Typhoon Bavi (2020) under the influence of the upper-level trough and the detached cutoff low from its base are investigated based on numerical experiments using the advanced Weather Research and Forecasting (WRF) model. Bavi formed over the western North Pacific between the Taiwan and Okinawa Islands on 23 August 2020. Under the influence of an upper-level trough to the north, Bavi initially moved northeastward. As the trough propagated eastward, a cutoff low was detached from the base of the trough on the next day. The downward penetration of the upper-level cutoff low led to a sudden northwestward turning motion of Bavi when it intensified to a severe typhoon and then moved almost due north and made landfall over North Korea. These changes and processes are well captured in a control numerical experiment. In a sensitivity experiment with the mid-latitude upper-level trough removed in the initial conditions, the TC moved primarily north-northeastward after one day simulation without the sudden northwestward turning. This track change led to an earlier landfall of the storm over South Korea and thus an earlier weakening than in the control experiment, which is termed the indirect effect on the storm intensity due to the change in the TC track. The results also show that eddy angular momentum flux convergence associated with the upper-level trough contributed little to the simulated TC intensification while the environmental VWS is key to the intensity change of Bavi.